Highly chemoselective direct crossed aliphatic- aromatic acyloin condensations with triazolium-derived carbene catalysts - CONNON, STEPHEN; GUNDALA , SIVAJI (My University, 2011)
It has been shown for the first time that triazolium pre-catalysts promote (in the presence of base) highly chemoselective crossed acyloin condensation reactions between aliphatic and ortho-substituted aromatic aldehydes. An o-bromine atom can serve as a temporary directing group to ensure high chemoselectivity (regardless of the nature of the other substituents on the aromatic ring) which then can be conveniently removed. The process is of broad scope and is operationally simple as it does not require the preactivation of any of the coupling partners to ensure selectivtiy. Preliminary data indicates that highly enantioselective variants of the reaction are feasible using chiral pre-catalysts.
PUBLISHED
Keywords: Chemistry; enantioselective; Nanoscience & Materials